Cruentas guerras: índios e portugueses nos sertões do Maranhão e Piauí (primeira metade do século XVIII) - MELO, Vanice Siqueira de (Universidade Federal do Pará, 2014)
In the captaincies of Maranhão and of Piauí, in Portuguese America, there were many wars against Indians throughout the first half of the eighteenth century. This dissertation discusses how the space of these captaincies was described in colonial texts, as well as how the troops contributed to transform the landscape of the region. This dissertation examines how the colonial landscape was composed both by the Indians spaces and by the relationship that indigenous groups established with each other and with Luso-brazilian settlers. This dissertation also discusses how the wars were part of power relations within the State Maranhão and Grão-Pará and how their occurrence depended on specific political interests.